Salib dan Keselamatan: Kritik Biblika terhadap Soteriologi Kristen Progresif - Avlorina, Mey (Sekolah Tinggi Teologi Injili Indonesia Palu, 2025)
Progressive Christianity promotes an inclusive theology of salvation that reinterprets the concept of redemption, rejecting the necessity of Christ’s atoning sacrifice on the cross. This perspective shifts the focus from faith in Jesus Christ as Lord and Saviour to self-transformation through social justice and moral actions. As a result, the meaning of the cross is marginalised, and salvation is perceived as a personal journey rather than divine redemption from sin. This study aims to critically analyse the Progressive Christian interpretation of salvation and evaluate it biblically. A qualitative research approach was employed, using a literature review to examine theological sources relevant to the topic. The findings indicate that sin necessitates atonement for salvation, the cross is central to Christ’s redemptive work, and salvation is found exclusively in Jesus Christ (Acts 4:12). This study concludes that the Progressive Christian understanding of salvation, which diminishes the significance of the cross, contradicts biblical teachings. Salvation is not merely about social transformation but is fundamentally dependent on Christ’s atoning sacrifice.